2016
DOI: 10.26719/2016.22.7.440
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of severe acute respiratory infection-associated hospitalization in Yemen, 2014/15

Abstract: Yémen : caractéristiques des cas d'hospitalisation associés aux infections respiratoires aiguës sévères, 2014-2015RÉSUMÉ Cette étude présente les agents étiologiques, les données démographiques des patients, la saisonnalité et les pathologies sous-jacentes chez des patients hospitalisés en raison d'infections respiratoires aiguës sévères (IRAS) au Yémen. Nous avons réalisé une analyse descriptive rétrospective des données portant sur les IRAS et couvrant la période de janvier 2014 à décembre 2015. Des sécrétio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…This result was similar to previously reports in Yemen and Jordan. 10,12 About 50% of cases were males, a finding that is similar to what had been reported from Mediterranean region. 7…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This result was similar to previously reports in Yemen and Jordan. 10,12 About 50% of cases were males, a finding that is similar to what had been reported from Mediterranean region. 7…”
Section: Discussionsupporting
confidence: 87%
“…Few studies were carried out to describe the mortality after influenza epidemic, 8 estimate the proportion of influenza and noninfluenza viruses and mortality among SARI patients, 9 and to understand the clinical characteristics of SARI associated with most detected pathogens during 2014-2015. 10 Still, there is gap in the information related to the role of influenza and noninfluenza viruses in severe outcome of SARI and associated factors. This study aimed to determine the proportions of influenza and noninfluenza virus among SARI patients, and assess the severity of SARI and its associated factors in Yemen.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that seasonal influenza infection is aggravated by existing chronic illness, with diabetes as the most frequently reported chronic condition among patients with severe influenza infection. 23 This necessitates the early detection and treatment with antivirals in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] In the same issue of the EMHJ, influenza outbreak characterization from other regional countries such as Jordan, lebanon, Morocco, and yemen were also published. [21][22][23][24] This is a step forward in the Eastern Mediterranean region; however, to establish effective prevention policies, more data including the health and economic burden of influenza over several seasons in the regional countries is needed.…”
Section: Discussionmentioning
confidence: 99%